The ampliatus species group of Ommatius Wiedemann, 1821 (Diptera, Asilidae, Ommatiinae) in Peru with the description of four new species - Sánchez, Pável; Camargo, Alexssandro (Zootaxa, 2023)
In this work, four new species of Ommatius are described from Peru; Ommatius amaru sp. nov. from Cuzco, Ommatius kuntur sp. nov. from Ayacucho and Cuzco, Ommatius uturuncu sp. nov. from Ayacucho and Pasco, and Ommatius yanantin sp. nov. from Cajamarca. All belong to the ampliatus species group, which is part of the holosericeus complex. Illustrations of external morphology, as well as dissected terminalia, are provided. A taxonomic discussion is given for all new species. A distribution map for the Peruvian species in the ampliatus group and an updated key to all species in this group are also given. The new species are named as a tribute to the Andean cosmovision which is based on thousands of years of pre-Columbian culture.